Judicial tools in the development of civil law rules (France as a model) - حسن, حيدر فليح (Journal of Legal Sciences, 2020)
Despite the principle of separation of powers brought by the French Revolution, which entrusted the task of drafting legislation and its amendment to the legislative authority and the task of settling disputes and settling them in the judiciary. However, since that date, the French judiciary has played a major role in the development of French civil law (In spite of all the economic and social developments that have taken place in French society throughout these years) since its promulgation until February of 2016, the date of the Legislative Decree No. 131 of the year 2016 A modification is the largest in the history of the French Civil Code (which was the judicial precedents in which a significant impact), was assisted by the French judiciary in the performance of the most important developmental task with tools of interpretation, measurement, and the exception, and tummy tuck. From here, this research came to highlight these four instruments and their role in the development of the rules of French civil law.